1993
DOI: 10.1002/j.1460-2075.1993.tb06217.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the M(r) 46,000 mannose 6-phosphate receptor gene in mice results in misrouting of lysosomal proteins.

Abstract: Lysosomal enzymes containing mannose 6‐phosphate recognition markers are sorted to lysosomes by mannose 6‐phosphate receptors (MPRs). The physiological importance of this targeting mechanism is illustrated by I‐cell disease, a fatal lysosomal storage disorder caused by the absence of mannose 6‐phosphate residues in lysosomal enzymes. Most mammalian cells express two MPRs. Although the binding specificities, subcellular distribution and expression pattern of the two receptors can be differentiated, their coexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 17 publications
2
63
0
2
Order By: Relevance
“…The targetting vector was linearized with NotI and introduced into the ES cell line E14-1 (7). Electroporation, culture, and selection conditions have been described (7,8). Colonies selected with G418 and gancyclovir were screened by Southern blot analysis of DNA digested with EcoRI and hybridization with the external 3Ј probe (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The targetting vector was linearized with NotI and introduced into the ES cell line E14-1 (7). Electroporation, culture, and selection conditions have been described (7,8). Colonies selected with G418 and gancyclovir were screened by Southern blot analysis of DNA digested with EcoRI and hybridization with the external 3Ј probe (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Among 89 colonies examined, two targeted clones were identified and injected into blastocysts of C57BL͞6J mice as described (8). Chimeric male mice were bred with C57BL͞6J females and the offspring was analyzed by Southern blot analysis of tail DNA for the presence of the homologously recombined ASA gene.…”
Section: Methodsmentioning
confidence: 99%
“…After 6, 12, and 24 h, samples of the medium were removed and cells were washed, scraped, and homogenized in TBS/1% Triton X-100. Lysosomal enzyme activities were detected using fluorometric and colorometric assays as described (Kö ster et al, 1993). To avoid a possible effect of the medium change leading to nonspecific increase of lysosomal enzyme activities, the enzyme activity in the medium after 6-h culture was withdrawn from the specific activities measured in the medium after 12 and 24 h. In each experiment the enzyme activities were measured from two parallel culture dishes.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Mice deficient in MPR46 and/or M6P/IGF2R have been generated (Köster et al, 1993;Ludwig et al, 1993;Ludwig et al, 1994). Studies on MPR46-and/or M6P/IGF2R-negative fibroblasts have indicated that both receptors are necessary for efficient lysosomal targeting.…”
Section: Introductionmentioning
confidence: 99%